The Parenthood Penalty in Mental Health: Evidence from Austria and Denmark - Alexander Ahammer; Ulrich Glogowsky; Martin Halla; Timo Hener (Institute of Labor Economics (IZA), 2023)
Using Austrian and Danish administrative data, we examine the impacts of parenthood on mental health. Parenthood imposes a greater mental health burden on mothers than on fathers. It creates a long-run gender gap in antidepressant prescriptions of about 93.2% (Austria) and 64.8% (Denmark). These parenthood penalties in mental health are unlikely to reflect differential help-seeking behavior across the sexes or postpartum depression. Instead, they are related to mothers' higher investments in childcare: Mothers who take extended maternity leave in quasi-experimental settings are more likely to face mental health problems.
Keywords: D63; J13; I10; J16; J22; 330; gender equality; fertility; parenthood; motherhood; mental health; parental leave